Analisa Keuntungan Merjer, dan Konglomerasi Pada Skala Ekonomi - Eksel Perdian Anggara; Muhammad Yasin (Jurnal Riset Akuntansi, 2025)
Analysis only to reach, industries often adopt patterns such as conglomeration or merger to improve and strengthen their market stability. Conglomeration and merger are key concepts in industrial growth. Merger itself involves the unification of two new different industries to achieve greater efficiency. In the context of economies of scale, companies can save costs by increasing production, expanding factories, or increasing their market share through the implementation of merger and conglomeration strategies. Industry analysis is also an important step in optimizing the implementation of this